Fractal Structures. Understanding the Geometries of Nature (diségno, 2026)
The observation of nature has historically guided design disciplines, from the proportional harmony of antiquity to the empirical studies of the Renaissance, which laid the groundwork for the development of biology and bionics. In the 20th century, the formulation of fractal geometry and the emergence of computer science made it possible to describe and simulate complex systems, going beyond formal imitation to investigate the processes of growth, adaptation and self-organisation characteristics of living organisms. Mandelbrot’s research has enabled the quantitative interpretation of morphogenetic phenomena in the natural world, highlighting fractal rules common to both animal and plant systems. The history of architecture is full of examples of the unconscious adoption of self-similar logic, which can now be reinterpreted using algorithmic and parametric modelling tools. This article proposes a reinterpretation of organic models and construction archetypes, such as brick, within a design paradigm based on computational morphogenesis, in which natural principles are transformed into operational protocols capable of combining formal complexity, structural efficiency and construction innovation.
Keywords: computational morphogenesis; fractal geometry; computational design; brick; construction archetypes